Statin therapy in atherosclerosis prevention: modern strategy and tactics - M. G. Bubnova (Кардиоваскулярная терапия и профилактика, 2009)
The article is devoted to modern approaches to lipid-lowering therapy. The role of statins in primary and secondary prevention of atherosclerotic pathology is described. The author presents modern views on the choice of the statin dose optimal for maximal preventive cardiovascular effect.